1983
DOI: 10.1002/ajmg.1320160410
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic heterogeneity in neural tube defects: A clue to causal heterogeneity

Abstract: We report here retrospective data on 991 liveborn and stillborn infants with neural tube defects (NTDs) born to Utah residents from January 1, 1940 to December 31, 1979. Data were obtained from multiple sources including approximately 1.25 million vital statistics records and several hundred physician and hospital charts. Causal heterogeneity among NTD patients is presumed because 6% of our cases have other congenital anomalies not part of the NTD field defect. A significant association of NTDs with oral cleft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 6 publications
2
9
1
Order By: Relevance
“…9,10 This observation contrasts with that of the present study, in which the sex ratio is the same overall and with each of the defects except among anencephalic babies, who were all females.…”
Section: Discussioncontrasting
confidence: 56%
“…9,10 This observation contrasts with that of the present study, in which the sex ratio is the same overall and with each of the defects except among anencephalic babies, who were all females.…”
Section: Discussioncontrasting
confidence: 56%
“…We have noted female predominance in the rates of myelomeningocele and anencephaly which seems to be a universal feature [14], whereas encephalocele occurred at equal frequencies in both sexes. The site of the lesion in spina bifida cystica cases was predominantly located in the dorsolumbar region and that of encepaloceles was located in the occipital region (Table 3).…”
Section: Discussionmentioning
confidence: 62%
“…The majority of previous studies investigating the genetic basis of NTDs have even been conducted on total NTDs (Barber et al, 2000;Boyles et al, 2006;Mitchell et al, 2009). However, it has recently been shown that NTDs show etiological heterogeneity that depends not only on the different NTD phenotypes, but also on the presence of associated defects (Khoury et al, 1982a(Khoury et al, , 1982bMartin et al, 1983;Relton et al, 2003). The present analysis of 308 DNA samples from subjects of the Lvliang mountain area of Shanxi Province in northern China, which has the highest rate of NTDs in the world, is the first maternal genetic association analysis to investigate a relationship between PCMT1 polymorphisms and NTDs in Chinese population.…”
Section: Discussionmentioning
confidence: 97%